2002
DOI: 10.1300/j013v36n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behavior of Women Ages 65 and Older on Mammography Screening and Medicare: Results of a National Survey

Abstract: (1) Highlight that breast cancer risk increases with age (and does not decline in the absence of risk factors) and communicate the correct frequency for having mammograms; (2) expand primary care physicians' roles in promoting mammography screening for women 65+; and (3) provide Medicare coverage information to older women, particularly those not taking advantage of this benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Literature has reported that elderly women are less likely to participate in mammography screening [6][7][8] However, it has been difficult to establish what exactly constitutes "elderly" or "older age" because various studies have employed different age ranges. Studies from the US have used cut offs such as 65+ and 80+, whereas Canadian studies tend to be restricted to the 50-69 age range.…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…Literature has reported that elderly women are less likely to participate in mammography screening [6][7][8] However, it has been difficult to establish what exactly constitutes "elderly" or "older age" because various studies have employed different age ranges. Studies from the US have used cut offs such as 65+ and 80+, whereas Canadian studies tend to be restricted to the 50-69 age range.…”
Section: Agementioning
confidence: 99%
“…One study found that women 65 years of age or older are less likely to attend mammography screening compared to younger women, as older women may be "less concerned" about mammography screening due to lack of symptoms and knowledge about age as a risk factor for breast cancer [6]. Older women are more likely to attend screening if it was recommended by their doctor; they seem to prefer a doctor's recommendation over media, family, or friends [7].…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…A recent UK survey (conducted in 2007) found that awareness of NHS cancer screening programs for breast and cervical cancer were lower among women aged 65 years than among younger women (unpublished data). In the US, a random digit dialing telephone survey of women aged 65 years 59 found that awareness of Medicare reimbursement for mammography was >75%, but minority women were twice as likely to be unaware of it as other women. 60 The authors pointed to the need to provide information to older women about Medicare coverage, particularly in cases in which they were not claiming reimbursement for screening.…”
Section: Awareness Of the Availability Of Screeningmentioning
confidence: 99%
“…For example, Eisner et al 59 found that approximately one-third of their sample (aged 65 years) said they were not as concerned about getting breast cancer as they had been when they were younger, and this proportion was higher among women aged 70 years than among those ages 65 years to 69 years. The perceived threat and hence the fear associated with cancer therefore appears to decrease with advancing age, although the authors noted that this reduction may reflect stronger beliefs in the efficacy of screening.…”
Section: Perceptions Of Cancermentioning
confidence: 99%